Speaking fluency and EFL learners’ reluctance to speak english among primary school students: factors and evidence - Desiana Safitri; Misdi Misdi (ETERNAL (English Teaching Journal), 2021)
Speaking is productive skill that use of utterance as the way to do communication and express the meaning with other people. Moreover, speaking English can be a bridge to communicate with foreigner. The writer wants to investigate what difficulties faced by students in speaking and what factors that influence students speaking ability. This research was descriptive qualitative research. It involved 25 students of a state junior high school in Indonesia and the participants were the eighth grade students. Observation and questionnaire were used to collect the data. The results showed that several issues of difficulties faced by students: fluency, hesitation, vocabulary, grammar, expression and pronunciation. It caused by varieties of factors, one of theme is students are seldom to discuss with their friends using English. The most factor that influences the speaking ability was cognitive factor where it involves the conceptualization, formulation and articulation when do to speak and student still not yet to do it well